Attachment at the transition to adolescence : concordance with concurrent maternal attachment and child's own attachment in infancy - Gaffney, Maureen (Trinity College (Dublin, Ireland). School of Psychology, 2000)
The study investigated three main sets of research questions derived from attachment theory developed by John Bowlby (1969/1982b, 1973, 1979, 1980, 1988) and Mary Ainsworth (1967, 1982; Ainsworth, Blehar, Waters, & Wall, 1978). The first and principal set of research questions investigated (a) the use of the Adult Attachment Interview (AAI: George, Kaplan, & Main, 1984, 1985, 1996) as an appropriate measure of attachment organisation in children aged 11-12; (b) the concurrent concordance between attachment organisation of the children and their mothers, also assessed on the AAI; (c) the concordance between the children’s attachment in infancy, assessed at 18 months in the strange situation (Ainsworth et al., 1978) and at age 11-12 on the AAI and (d) the concordance between infant attachment and maternal attachment assessed over 10 years later.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin